METAMORPHOSIS OF HIGHER EDUCATION: NAVIGATING COMPLEXITY THROUGHINTERDISCIPLINARY PEDAGOGY AND CUTTING-EDGE TECHNOLOGICAL INTEGRATION FOR GLOBAL EXCELLENCE - Loso Judijanto; Fadli Firdaus; Jhon Hericson Purba; Kori Puspita Ningsih; Najamuddin Petta Solong (Adisam Publisher, 2023)
Amid the intricate tapestry of higher education's metamorphosis, a profound paradigm shift unfolded, weaving together interdisciplinary pedagogy and avant- garde technological advancements. This transformative journey scrutinized through a meticulous literature review methodology, unraveled the dynamic interplay between evolving pedagogical approaches and the seamless integration of cutting- edge technologies. In navigating the intricate complexities inherent in contemporary education, the study meticulously elucidated pivotal trends, delineated the nuanced role of interdisciplinary pedagogy and critically assessed the far-reaching impact of technological integration on global academic standards. The research uncovered a discernible evolution in pedagogical strategies, amplifying the clarion call for collaboration across diverse disciplines. This collaborative ethos, a hallmark of interdisciplinary pedagogy, emerged as a potent driving force fostering educational and holistic student learning experiences. The findings, akin to a compass guiding higher education's trajectory, underscored the strategic adoption of cutting-edge technologies. With their transformative influence on teaching methodologies, these technological enablers became keystones in the global collaboration mosaic within the academic sphere. As the study meticulously unveiled the layers of this educational transformation, it became evident that the fusion of interdisciplinary pedagogy and cutting-edge technology constituted more than a mere convergence. It represented a synthesis—a harmonious orchestration of diverse elements shaping the future contours of higher education. In this symphony of change, the resonance of collaboration, facilitated by interdisciplinary pedagogy, harmonized with the cadence of technological prowess, creating a transformative melody reverberating across the academic landscape.